A proposal towards resilient complex networks through evaluation and adaptation mechanisms - Cinara Guellner Ghedini (2012)
Attacks and failures tolerance of complex networks is related to the concept of vulnerability in different contexts, from biology and sociology to computer science and physics. Studies have revealed that the topologies of these networks are inherently vulnerable to failures of central elements. Complex adaptive systems, emergent in nature, are considered more resilient because, despite facing periodic changes, have the ability to maintain their main topological properties. Inspired by these systems and with the purpose of providing more robust communication networks, this work proposes mechanisms for evaluating fault tolerance of complex networks topologies and procedures for promoting the necessary adjustments to maintain their main topological properties. The performance of the proposed mechanisms showed that failures of central elements can lead to a global state of vulnerability. In such a state, evaluation and adaptation processes are more likely to miscarry. The resulting model also serves as a tool for the computational modelling of problems of vulnerability in several application contexts.